OUTCOMES OF RETINAL DETACHMENT REPAIR AFTER POSTERIOR OPEN GLOBE INJURY. Issue 4 (April 2016) - Reed, David C.; Juhn, Alexander T.; Rayess, Nadim; Hsu, Jason; Chiang, Allen
Abstract : Purpose: To report outcomes of retinal detachment (RD) repair following posterior open globe injury. Methods: This retrospective, consecutive case series examined patients who underwent RD repair following Zone II and/or III open globe injury repair between January 1, 2007 and October 31, 2013. Patients with <3 months of follow-up since their last vitreoretinal surgery, and those who underwent pars plana vitrectomy (e.g., for intraocular foreign body) during their initial open globe injury repair were excluded. Results: Of 30 patients who met inclusion criteria, reattachment of the retina was achieved in 25 (83%) during the first vitreoretinal surgical procedure and 5 (17%) were deemed inoperable intraoperatively. Ten patients (30%) developed recurrent RD, and 8 underwent additional surgery. At last follow-up, reattachment was observed in 4 of these 8. The overall rate of final reattachment was 63% (19 patients). The mean number of surgeries for RD was 1.5 (range, 1–3). Fifteen patients (50%) achieved final visual acuity of counting fingers or better. Mean follow-up from the last vitreoretinal surgery was 23 months (range, 3–52). Conclusion: Although RD following posterior open globe injury confers a grave prognosis, successful anatomic reattachment of the retina was achieved in the majority of patients in this series, with half achieving ambulatory vision. Abstract : This retrospective study assessed the outcomes of retinal detachment repair in 30 consecutive patients who had previously undergone repair of posterior open globe injury. At last follow-up, reattachment of the retina was observed in 19 (63%), and vision was counting fingers or better in 15 (50%).